TEACHING ENGLISH SPEAKING SKILL THROUGH CAKE APPLICATION FOR TENTH GRADE STUDENTS OF SMA MUHAMMADIYAH 1 UNISMUH MAKASSAR - Hasmin, Fauzia; Akib, Erwin; Maharida (FKIP Unismuh Makassar, 2024)
This research aims to find out is there any improvement of the students’ speaking accuracy especially in their vocabulary and pronunciation by using “CAKE” application for the tenth grade students of SMA Muhammadiyah 1 Unismuh Makassar. The researcher used a pre-experimental research using quantitative design. The population was the tenth grade students of SMA Muhammadiyah 1 Unismuh Makassar and the sample was X MIA class that was selected by using purposive sampling technique. The instrument used was speaking test which contain pre-test, treatment and post-test.The research findings indicated that the use of “CAKE” application in teaching speaking accuracy especially in vocabulary and pronunciation were giving significant effect to the students’ speaking ability. It was proved by the mean score of students speaking accuracy in vocabulary of the pre-test was 66.84 then improved to be 77.04 in post-test and the mean score of students’ speaking accuracy in pronunciation of the pre-test was 66.08 then improved to be 77.08 in post-test. In addition, t-test value higher than the t-table value (17.791>2,064). It means that there is an improvement by using “CAKE” application to improve students’ speaking accuracy in vocabulary and pronunciation.